The Influence of Service Quality Perception and KUR Loan Procedures on KUR Customers' Repurchase Intention Through Customer Satisfaction as a Mediating Variable at Bank Mandiri Purwakarta - Ria Malika Rohayati; Nugraha Saefudin (Dinasti Publisher, 2025)
This study aims to analyze the influence of service quality perception and loan procedures on repurchase intention, with customer satisfaction as a mediating variable at Bank Mandiri Purwakarta. The research employs descriptive and verificative analysis using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) approach. The results indicate that loan procedures have a positive and significant effect on repurchase intention, whereas service quality does not affect repurchase intention. Additionally, customer satisfaction is proven to be a mediating variable that strengthens the relationship between loan procedures and repurchase intention. This means that the better the loan procedures provided by the bank, the higher the customer satisfaction, ultimately increasing their repurchase intention. These findings imply that bank management should focus more on improving loan procedure standards to enhance customer satisfaction and strengthen repurchase intention